2017
DOI: 10.7150/ijbs.18045
|View full text |Cite
|
Sign up to set email alerts
|

Forsythoside A exerts antipyretic effect on yeast-induced pyrexia mice via inhibiting transient receptor potential vanilloid 1 function

Abstract: Transient receptor potential vanilloid 1 (TRPV1) is a non-selective cation channel gated by noxious heat, playing major roles in thermoregulation. Forsythoside A (FT-A) is the most abundant phenylethanoid glycosides in Fructus Forsythiae, which has been prescribed as a medicinal herb for treating fever in China for a long history. However, how FT-A affects pyrexia and what is the underlying molecular mechanism remain largely unknown. Here we found that FT-A exerted apparent antipyretic effect through decreasin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 29 publications
0
17
0
Order By: Relevance
“…Pyrexia in mice was induced as described by Liu et al [8] with minor modifications. The initial rectum temperature of each animal was measured using a lubricated digital thermometer.…”
Section: Anti-pyretic Activity In Brewer's Yeast Induced Pyrexia In Micementioning
confidence: 99%
“…Pyrexia in mice was induced as described by Liu et al [8] with minor modifications. The initial rectum temperature of each animal was measured using a lubricated digital thermometer.…”
Section: Anti-pyretic Activity In Brewer's Yeast Induced Pyrexia In Micementioning
confidence: 99%
“…Various studies have used this protocol after the injection of yeast and have induced the antipyretic drugs 21 . It was observed that Bacopa monnieri caused a significant (p<0.05) decrease in the rectal pyrexia which is also similar to the standard drug indomethacin Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In recent years, forsythoside A has been reported to exhibit multiple pharmacological activities, including anti-inflammatory [43][44][45][46][47][48][49], anti-endotoxin [50,51], antivirus [52], and antipyretic [53] effects, as well as preventing hippocampal injury [54]. It is a good candidate agent for treating inflammatory diseases [46], asthma [47], Ti implant-associated infection [48], bronchitis infection [52], pyretic disease [53], and Alzheimer's diseases [54]. In our study, we elucidated that the application of forsythoside A at a high concentration could disturb the function of the endothelial barrier and cause vascular leakiness.…”
Section: Discussionmentioning
confidence: 99%